A novel and high-efficient method for the preparation of heat-stable antifungal factor from Lysobacter enzymogenes by high-speed counter-current chromatography - Sun, Weibo; Tang, Bao; Dong, Liangliang; Xu, Jianhong; Zhao, Yancun; Liu, Fengquan (Frontiers in Microbiology, 2023)
Heat-stable antifungal factor (HSAF) produced by the biocontrol bacterium Lysobacter enzymogenes shows considerable antifungal activity and has broad application potential in the agricultural and medical fields, and there is a great demand for pure HSAF compound in the academic or industrial study. However, an efficient preparation method that produces high yield and high purity of HSAF is lacking in use, limited the development of HSAF to be a new drug. Here, high-speed counter-current chromatography (HSCCC) combined with column chromatography was successfully developed for the separation and preparation of HSAF from the crude extract of L. enzymogenes OH11. The crude extract was obtained by macroporous resin adsorption and desorption, and the main impurities were partly removed by ultraviolet light (254 nm) and gel filtration (Sephadex LH-20). In HSCCC procedure, the selected suitable twophase solvent system (n-hexane/ethyl acetate/methanol/water = 3:5:4:5, v/v, the lower phase added with 0.1% TFA) with a flow rate of 2.0 mL/min and a sample loading size of 100 mg were optimized for the separation. As a result, a total of 42 mg HSAF with the purity 97.6% and the recovery 91.7% was yielded in one separation. The structure elucidation based on HR-TOF-MS, 1 H and 13 C NMR and antifungal activities revealed that the isolated compound was unambiguously identified as HSAF. These results are helpful for separating and producing HSAF at an industrial scale, and they further demonstrate that HSCCC is a useful tool for isolating bioactive constituents from beneficial microorganisms.